Electrochemical characterization of various tin-based oxides as negative electrodes for rechargeable lithium batteries - Nam, SC; Paik, CH; Cho, WI; Cho, BW; Chun, HS; Yun, KS (ELSEVIER SCIENCE SA, 1999)
Tin oxide and tin-based composite electrodes are examined in both bulk and thin-film form for prospective use as negative electrodes for lithium rechargeable batteries. For bulk electrodes, tin oxides and Sn-Zn-P-O composite materials are compared by charge-discharge testings. Thin films of oxides and composite thin-film electrodes prepared by heat treatment (temperature and time) are characterized by X-ray diffraction analysis, Auger electron spectroscopy, and scanning electron microscopy. The characteristics of thin films are found to depend on the heat-treatment temperature, which influences the structure, the grain size, and adhesion to the substrate. Capacities higher than 350 mA h g(-1) are found for bulk electrodes beyond 20 cycles, and beyond 100 cycles for thin-film electrodes. (C) 1999 Elsevier Science S.A. All rights reserved.